Perspektif HTN terhadap Penerapan PP No. 21 Tahun 2020 tentang PSBB Di Kabupaten Paluta - Ali Wardana Pohan (Inovasi Pratama Internasional. Ltd, 2022)
The spread of Covid-19 is increasing which has an impact on the economy, social, security and welfare of the community. The problem to be studied is how the substance of PP no. 21 of 2020 in terms of Law no. 12 of 2011 concerning the Establishment of Legislation, and its legal implications for the implementation of PSBB for a region. This type of research is normative juridical, namely research based on law and empirical juridical, namely by conducting interviews. Based on the results of the study, regarding the substance of PP No. 21 of 2020 in terms of Law no. 12 of 2011 is not in accordance with the principle of the formation of laws and regulations. PP No. 21 of 2020 as the Implementing Regulation of Law no. 6 of 2018 concerning Health Quarantine is only a reduplication of Law no. 6 of 2018. The implementation of the law regarding the application of PSBB for an area in the context of implementing the policy to accelerate the handling of Covid-19 in North Padang Lawas Regency is the restriction of population activities in an area as stated in the North Padang Lawas Regent's Instruction Number 7 of 2022 concerning the Enforcement of Restrictions Community Activities. Level 2 and Optimization of the Covid-19 Handling Command Post at the Village and District Levels to Control the Spread of Covid-19 in North Padang Lawas Regency.